1976
DOI: 10.1210/jcem-43-6-1250
|View full text |Cite
|
Sign up to set email alerts
|

Androgens in Patients with Benign Prostatic Hyperplasia Before and After Prostatectomy

Abstract: Plasma androgens [testosterone (T), 17beta-hydroxy-5alpha-androstan-3-one (DHT), androst-4-en-3,17 dione(A), and dehydroepiandrosterone (DHEA)] as well as 17 hydroxyprogesterone were measured in a group of patients (age 60-80 yrs.) with benign prostatic hyperplasia (BPH) just before prostatectomy and compared to values obtained in subjects of similar age without signs of BPH. The most important difference was observed in the mean DHT level which was significantly (P less than 0.025) higher than in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
3

Year Published

1979
1979
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 0 publications
5
35
3
Order By: Relevance
“…Up to now, however, few data have linked aberrations of these hormones to the development of BPH [7, 8, 9, 10, 11, 12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, however, few data have linked aberrations of these hormones to the development of BPH [7, 8, 9, 10, 11, 12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, the concentration of dihydrotestosterone is elevated in the hyperplastic prostates of man (10,11) and dog (12,13). Third, the plasma levels of dihydrotestosterone are elevated in men with hyperplastic prostates (14,15). Fourth, both canine and human prostatic hyperplasia are accompanied by an increase in the activity of 3a-hydroxysteroid dehydrogenase (16, 17), and (in the human prostate at least) this increased activity is paralleled by a decreased tissue concentration of 3a-androstanediol (11).…”
Section: Introductionmentioning
confidence: 99%
“…In 1975 we first reported that in the face of normal or reduced total testosterone levels in healthy elderly men with BPH studied in a retirement home, plasma DHT levels were significantly increased and the data indicated the presence of a separate population as compared with younger men [42], This observation has now been con firmed by five other groups [39,41,43]. Vermeulin and DeSy [39], in confirming our data, were able to study a group of aged-matched controls without clinical evidence of BPH.…”
Section: Changes In Circulating Hormones In Bph Patientsmentioning
confidence: 89%
“…Estradiol in plasma tends to increase [36,37] and this in part is due to increased sex hormone binding pro tein (SHBG) concentration [1], Testosterone and in par ticular free testosterone levels fall in men 60-80 years of age [38,39], This remains controversial since unusually healthy men especially selected for their excellent health may not show these changes [40], However, an unselected group of outpatients probably more representative of the aging population show reduced testosterone levels. In a recent study from our laboratory a small group of men 65 years of age had normal plasma testosterone but clearly reduced secretion rates; the result of reduced testosterone clearance [41].…”
Section: Hormonal Changes In the Aging Malementioning
confidence: 99%